1989
DOI: 10.1111/j.1365-2605.1989.tb01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Immuno‐competent cells in the murine epididymis

Abstract: Cryostat sections of epididymides from mice were stained with monoclonal antibodies against immuno-competent cells. This investigation was undertaken to gain basic data about the distribution of macrophages. T lymphocytes, MHC class II and MIF in the normal murine epididymis to establish the mouse as a model for immunological epididymal research. The most important findings were as follows. (1) Macrophages, T lymphocytes, MHC class II and MIF positive cells were distributed similarly in the caput, corpus and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 35 publications
5
61
0
1
Order By: Relevance
“…In the human epididymis, immunocytochemical studies using antibodies to various leukocyte markers revealed T helperhnducer lymphocytes in the interstitium, whereas the majority of lymphocytes in the epithelium were the suppressor/cytotoxic variety and were thought to form part of a n immunological barrier by preventing the development of an immune response to autoantigens on luminal spermatozoa (El-Demiry et al, 1985;Ritchie et al, 1984). In contrast, macrophages were the main immunologic cell type detected in the normal mouse epididymidis (Nashan et al, 1989). Furthermore, immunocytochemical studies in mice showed that vasectomy resulted in a n immunologic response in which macrophages and MHC class I1…”
Section: Cells Of the Lnfersfifial Reactionsmentioning
confidence: 77%
“…In the human epididymis, immunocytochemical studies using antibodies to various leukocyte markers revealed T helperhnducer lymphocytes in the interstitium, whereas the majority of lymphocytes in the epithelium were the suppressor/cytotoxic variety and were thought to form part of a n immunological barrier by preventing the development of an immune response to autoantigens on luminal spermatozoa (El-Demiry et al, 1985;Ritchie et al, 1984). In contrast, macrophages were the main immunologic cell type detected in the normal mouse epididymidis (Nashan et al, 1989). Furthermore, immunocytochemical studies in mice showed that vasectomy resulted in a n immunologic response in which macrophages and MHC class I1…”
Section: Cells Of the Lnfersfifial Reactionsmentioning
confidence: 77%
“…The human epididymal epithelium was reported to contain suppressor/cytotoxic lymphocytes (CD81), whereas helper/inducer lymphocytes (CD41) were detected in the interstitium; it was suggested that these cells functioned as part of an immunological barrier in the epididymis (Ritchie et al, 1984;El-Demiry et al, 1985), although other authors have questioned whether these lymphocyte subtypes are strictly compartmentalized (Pudney and Anderson, 1993). On the other hand, macrophages were the predominant cell type detected immunocytochemically in the normal mouse epididymis (Nashan et al, 1989). CD4-positive helper/inducer lymphocytes and macrophages were reported to be more numerous than CD8-positive suppressor/cytotoxic lymphocytes in the epididymis of the Wistar rat (Hooper et al, 1995).…”
mentioning
confidence: 99%
“…T cell subsets have been localized in the male reproductive tract of humans (Yeung et al, 1994), rat, rhesus monkey (Dyme and Romrell, 1975;Flickinger et al, 1997) and mouse (Nashan et al, 1989). Also, we have localized T cell subsets in the rooster testis and seminal tract (Yoshimura et al, , 2005.…”
Section: Introductionmentioning
confidence: 93%